Assuming the interest is simple interest, as opposed to compound interest,
Answer:
g(-1) = -5
g(2a+1) = 16a+11
Step-by-step explanation:
Substitute the given value into the function and evaluate.
So for g(x) = 8x+3
You substitute g(-1)
So g(-1) = 8(-1)+3
That is how you get -5
Then g(2a+1)
So g(2a+1) = 8(2a+1)+3
Thats how you get 16a+11
Hope this helps. Mark as brainlist
Answer:
It took 2 hours longer
Step-by-step explanation:
Answer:
X = i don't know
Y = 50°
Step-by-step explanation:
dugobdddjcjcfsfhjjgkcfzdd
Answer:
1. -9xy
2. 6ab
3.-8mn
4. 17nx
Step-by-step explanation: